Pengaruh Komunikasi Kepala Sekolah Terhadap Prilaku Toleransi dan Disiplin Kerja Guru di Sekolah Dasar Negeri Bernas - Marzuki Marzuki (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the effect of principal communication on teachers’ tolerance behavior and work discipline at Bernas Public Elementary School. The background of the study is based on preliminary observations indicating several issues, such as teachers’ tardiness, insufficient lesson preparation, and limited ability to accommodate student diversity. This research employed a quantitative approach using a survey method. The population consisted of all 32 teachers at Bernas Public Elementary School, and total sampling was applied. Data were collected through questionnaires and documentation, while data analysis included a normality test and a paired sample t-test. The results revealed that principal communication had a significant effect on teachers’ tolerance behavior and work discipline, with a significance value of 0.000. The mean score of teachers’ tolerance behavior was 80.07, while the mean score of work discipline was 84.68. The novelty of this study lies in emphasizing the strategic role of principal communication in simultaneously fostering tolerance and discipline among teachers. The practical implications indicate that effective, open, and continuous communication from school principals can create a conducive working environment and enhance teacher professionalism. This study contributes to the development of elementary school management, particularly in strengthening leadership communication practices in educational settings.